Indigenous Lands are Better for Amphibian Biodiversity Conservation Than Immigrant-Managed Agricultural Lands: A Case Study From Manu Biosphere Reserve, Peru. (13th October 2022) - Serrano-Rojas, Shirley J.; Whitworth, Andrew; Paredes-Garcia, Julio A.; Pillco-Huarcaya, Ruthmery; Whittaker, Lawrence; Huaypar-Loayza, Karl H.; MacLeod, Ross
The efficacy of protected areas is tied to the management of surrounding areas. Still, the importance of buffer zones for biodiversity conservation is overlooked. Manu Biosphere Reserve is one of the most biodiverse places on earth, yet destructive land-use practices are degrading the ecological integrity of its buffer zone. To better understand the importance of different land-uses within Manu's buffer zone for biodiversity conservation, we assessed amphibian communities across a land-use gradient in the buffer zone (immigrant agricultural land, forests used by three Indigenous communities, and a regenerating forest), in addition to a reference site in its core protected area. We surveyed six sites and sampled amphibian communities using visual encounter surveys and leaf litter searches over dry and wet seasons. Overall, in 2249 ha surveyed of the buffer zone, we recorded 70 amphibian species (57% of the 124 species recorded in the Manu Biosphere Reserve from the same elevational range within our study). Species richness, evenness, and diversity of amphibians decreased with habitat degradation and were lowest in the agricultural land. Conversely, the richness and diversity of amphibians in the regenerating forest and the Indigenous communities' forests were similar to that of the core protected area, and each had a relatively unique community composition, whereas the agricultural land was dominated by generalist species. Our results suggest that increasing degradation through expanding agriculture traditionally adopted by immigrant communities could significantly threaten biodiversity within the buffer zone. However, our findings also underscore the high potential of buffer zones managed by Indigenous communities for biodiversity conservation. A combination of sustainable livelihood activities, cultural practices, and forest protection, as observed in many Indigenous communities, is critical to fulfilling the role of a Biosphere Reserve—to reconcile the conservation of biological and cultural diversity while improving social and economic development.